RP-HPLC Method Development and Validation of Dapagliflozin in Bulk and Tablet formulation - Jeyabaskaran.M,; Prof.Rambabu.C,; Dhanalakshmi.B, (IJPAR JOURNAL, 2013)
The present work is concerned with application of simple, precise, accurate, reproducible and specific RP - HPLC method for estimation of dapagliflozin (DGF) in bulk and pharmaceutical dosage forms using an Hypersil BDS 250mm x 4.6 mm, 5 column in isocratic mode with 0.1% Ortho phosphoric acid buffer and acetonitrile 50:50 % v/v as mobile phase at a flow rate of 1ml/min. The injection volume was 10 µl and the total runtime was set as 5min. The determination of analytes was carried out at 245nm using PDA detector. The retention time for DGF was found to be 2.226min. The proposed method has permitted the quantification of DGZ over linearity in the range of 25 – 150 µg/ml and its percentage recovery was found to be 100.12 %. The % RSD of intraday and inter day precision were found 0.6% and 0.29%.